CFD-Based Flow Field Characteristics of Air-Assisted Sprayer in Citrus Orchards - Xiangfei Huang; Yunwu Li; Lang Chen; Kechao Wang (Agriculture)
Air-assisted sprayers are an essential piece of equipment for improving spraying efficiency and pesticide utilization; their performance directly affects the effectiveness of pesticide application. This study, addressing the plant protection needs of hilly citrus orchards, designed an air duct structure for an air-assisted sprayer and analyzed its airflow characteristics and droplet deposition effects based on CFD simulation technology. The reliability of the simulation results was verified through air speed boundary tests, revealing that the maximum effective boundaries of the integrated air duct and the independent air duct in different directions were 18.4 cm and 17.2 cm, respectively, providing a reference for the spatial arrangement of the air duct. The study indicates that properly matching the fan speed, spray pressure, and spray distance could optimize droplet deposition, enhance spray uniformity, and improve pesticide utilization. However, excessively high fan speeds (>6000 r/min) or spray pressures (>0.8 MPa) may reduce droplet transport efficiency. This research provides theoretical support for the design and parameter optimization of sprayers in hilly citrus orchards.